Revisiting the concepts of money, profit and interest from the perspective of value and diminishing marginal utility - Mydin Meera, Ahamed Kameel; Mubasheera, Hamida (Center for Central Banking Research and Education, Bank Indonesia, 2015)
This article is a theoretical article that attempts to clarify the inherent meanings of the concepts of profit and interest, i.e. two important concepts in finance, particularly Islamic Finance. These are age-old concepts in economics that still draw confusion among people. Profit comes from trade and interest comes from lending and borrowing activities. While the former is much encouraged in Islam, the latter is strongly forbidden. Nonetheless, in today’s monetary and financial circumstances, the market interest rate is being used as a benchmark for the Islamic profit rate, drawing criticisms from many quarters that both are indeed one and the same. Using the fundamental economic concept of marginal utility, this paper attempts to clarify the fundamental difference in these two concepts and their implications for modern finance, particularly Islamic finance. Indirectly in the process, the paper also clarifies the concepts of money and riba.